Recent Advances in Nanocarrier-Assisted Therapeutics Delivery Systems - Shi Su; Peter M. Kang (Pharmaceutics, 2020)
Nanotechnologies have attracted increasing attention in their application in medicine, especially in the development of new drug delivery systems. With the help of nano-sized carriers, drugs can reach specific diseased areas, prolonging therapeutic efficacy while decreasing undesired side-effects. In addition, recent nanotechnological advances, such as surface stabilization and stimuli-responsive functionalization have also significantly improved the targeting capacity and therapeutic efficacy of the nanocarrier assisted drug delivery system. In this review, we evaluate recent advances in the development of different nanocarriers and their applications in therapeutics delivery.